Exploring Childbirth Trends and Maternal Awareness in Libya: Cross Sectional Study and Narrative Review (2014-2023) - Abdelghffar, Abdelghffar F.; Elfakhri, Amal A.; Alhawari, Rasha S. (Open Science Press, 2025)
This study explores childbirth trends and maternal awareness in Libya through an online survey of 578 Libyan women of childbearing age. The survey explored their pre-existing knowledge as well as their experiences in undergoing delivery methods. The findings reveal that while many women rely on doctors for guidance, a considerable number seek information from the internet which risks disseminating misinformation. Additionally, communication from healthcare providers regarding delivery options was often deemed insufficient. The study highlights the psychological challenges associated with childbirth, with many women expressing lack of adequate mental health support and concerns over the financial burden of cesarean deliveries. Awareness of legal rights also emerged as a pivotal factor in shaping maternal decisions. The data also show a frequency of C-sections, as reported by participants, reaching 60.8% for the first baby, and 52% for the second baby. In conclusion, the study underscores the need for improved maternal education, better psychological support, and targeted policy interventions to improve childbirth experiences and outcomes across the country.
Keywords: Childbirth; Maternal Awareness; Cesarean Sections; Obstetrics Services; Fertility Rates; Libya; Health System